Betel Leaf Ransing Admission on Decreasing Pathological Flour Albous In Girl Adolescent - Oktriani, Tuti; Wulandari, Safni (Jurnal Kesehatan - STIKes Prima Nusantara, 2018)
In Indonesia, 7 from 10 women experienced flour albous in 2004 One of the problems of reproductive health of teenagers especially the girl who often experience was pathological vaginal discharge. One of the nonpharmacological therapy was betel leaf stew. The purpose of this study was to know the effect of Giving Betel Leaves to Reducing White Pathology In Young girl In Boarding School Sumatra Thawalib Bukittinggi. This was a queasy experiment. The research with One Group Pre-Test-Post-Test Design. The population is female teenagers who experience pathological vaginal discharge at boarding School Sumatra Thawalib Parabek Bukittinggi. The sampling technique used consecutive sampling and the number of samples counted 14 people. Data collection was done by using the observation sheet and questioner. The result of a statistical test using paired T-test in the experimental group showed the comparison of pathological variance reduction before giving intervention in 4.71 and after giving betel left an average of 2.71, with p-value 0,0001. Based on the above results can be concluded that the decoction of betel leaf affects the reduction of pathological vaginal discharge in the experimental group. Suggestion to the respondent to be able to use the betel leaf stew in reducing pathological whiteness as nonfamakologis management because of the amount of content possessed by betel leaf Eugenol compound on betel leaf, proven to kill the fungus, tannin, is astringent, which reduces the secretion of fluid.